(untitled) (Journal of the College of Basic Education, 2022)
The Spanish is considered one of the most developed and renovated languages. Spanish language has gone through several stages since its separation from the mother language Latin until its current form. As the medieval Spanish was different of the Spanish that used in the Spanish golden epoch and this Spanish is different of current Spanish. These changes have included syntactical, morphological, phonetically, semantically and orthographical changes. One of the changes that have been happened in the Spanish language is the formal and informal forms of address. Through our research for these forms of address over eight centuries and in thirty-five literary works dispersed across these centuries, we found that the formal forms of address are the most changed. As from time to another new form appear and continue for a short period and then is replaced by another. Some of these forms have not been completely disappear, but, its derivation forms have been developed and survived until reached the current form, such as the formal form (usted formal you) where its roots attribute to the fifteenth century back. This form has taken many variations until it reached the current form that was used for the first time in the eighteenth century and still in use.